2008
DOI: 10.1002/jcc.21094
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations on halogen‐bonded complexes and comparison with density functional methods

Abstract: A systematic theoretical investigation on a series of dimeric complexes formed between some halocarbon molecules and electron donors has been carried out by employing both ab initio and density functional methods. Full geometry optimizations are performed at the Moller-Plesset second-order perturbation (MP2) level of theory with the Dunning's correlation-consistent basis set, aug-cc-pVDZ. Binding energies are extrapolated to the complete basis set (CBS) limit by means of two most commonly used extrapolation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 95 publications
3
73
0
Order By: Relevance
“…It is well established that the second Møller-Plesset perturbation (MP2) method [29] is a proper method to study the complexes which including dispersion energy, it can provide good estimates of geometries and energies for noncovalent complexes [28,30]. The MP2 method with the augmented correlation-consistent polarized valencedouble/triplet (aug-cc-pVD/TZ) basis set has been successfully applied in order to reveal the nature of the halogen bond interaction [6,[31][32][33]. Therefore, we use the MP2 method with aug-cc-pVDZ atomic basis sets in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that the second Møller-Plesset perturbation (MP2) method [29] is a proper method to study the complexes which including dispersion energy, it can provide good estimates of geometries and energies for noncovalent complexes [28,30]. The MP2 method with the augmented correlation-consistent polarized valencedouble/triplet (aug-cc-pVD/TZ) basis set has been successfully applied in order to reveal the nature of the halogen bond interaction [6,[31][32][33]. Therefore, we use the MP2 method with aug-cc-pVDZ atomic basis sets in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen atoms were used as capping atoms. For the QM layer, two different density function theory (DFT) methods were employed: the widely used B3LYP method, and the MPWLYP method, which, in a recent benchmark study of halogen bonding, was shown to give accuracies close to those obtained using high-level correlated ab initio methods [30]. The standard 6-31G(d) basis set was used for 2UY3, 2VIV, 1G3M, 1G5F, 1UV5, 1N8U, and 2OXD, and the lanl2dz basis set was adopted for 1SN5 and 3E3D.…”
Section: Resolutionsmentioning
confidence: 97%
“…These quantum mechanical effects have led scientists to postulate the existence of the so-called C-X-O "halogen bonds" or "X-bonds". Such interactions cannot be captured by density functional theory (DFT) approaches, which have long been recognized as inadequate to account for dispersion forces [3]. They would require high-level (and costly) computational approaches such as those provided by coupled cluster methods (MP2) or third-generation dispersion-corrected DFT [1].…”
Section: Incorporating Quantum Mechanical Effects Into Drug Designmentioning
confidence: 99%